Otolith Growth-Check Patterns and Morphometric Relationships of Nile Tilapia (Oreochromis niloticus) from the Deli River Estuary, North Sumatra, Indonesia - Christina Sharon Aprilia Manalu; Deni Efizon; Efawani Efawani; M. Irsyad Nur (Jurnal Perikanan dan Kelautan, 2026)
Nile tilapia (Oreochromis niloticus) is tolerant of variable aquatic conditions, but fluctuations in growth can be recorded in the macrostructure of its otoliths. This study characterized sagittal otolith morphology, quantified fish–otolith morphometric relationships, described dark growth-check patterns, and evaluated concurrent water-quality conditions in the Deli River Estuary, Belawan Bahari, North Sumatra. Fifty fish (27 females and 23 males) obtained from four artisanal fishing occasions between October and December 2024 were measured for total length, body weight, otolith length, width, and weight. Length–weight relationships were estimated using W = aLᵇ, whereas total length–otolith relationships were assessed by linear regression. Fish measured 180–235 mm and weighed 152–300 g; sagittal otoliths were 4.30–6.77 mm long and 0.0063–0.0630 g in weight. The estimated length–weight exponent was 2.979 in females (95% CI: 2.545–3.414) and 2.463 in males (95% CI: 2.063–2.863), indicating near-isometric growth in females and negative allometry in males. Total length explained 78.4% of male otolith-length variation but only 13.9% in females. Dark growth checks ranged from zero to three; 45 fish (90%) had at least one check, and the first check occurred 0.225–0.300 mm from the nucleus. Temperature was 25–28 °C, pH was 6.0, and dissolved oxygen was 4.09 mg/L. The growth checks indicate episodes of reduced otolith accretion, but their causes and periodicity cannot be assigned without validation. Seasonal sampling, replicate readings, and otolith chemical or physiological analyses are recommended.